STATUS DAN KEDUDUKAN HUKUM LEMBAGA FINANCIAL TECHNOLOGY (FINTECH) SYARIAH DALAM MENYELENGGARAKAN JASA KEUANGAN KEPADA MASYARAKAT - Sumartini, Siti; Arifin, Jajang; Gatri Sagala, Stefani (Universitas Wiralodra, 2021)
The development and enthusiasm of the community towards the growth of sharia economic practices is very high, especially with the proliferation of the establishment of sharia financial institutions (LKS), one of which is sharia fintech. Sharia fintech is an innovation of sharia-based financial services by utilizing technological advances. In addition to providing offers and schemes that are different from conventional services, it also provides certain limitations on the use of funds provided by investors or lenders. In addition, the development of sharia fintech needs to be supported by the appropriate regulations and infrastructure. With the support for these two aspects, the actors and service users of Islamic financial institutions will have the convenience of meeting the needs of financial access. Access to these financial needs in its development has become increasingly complex and diverse. In this case, the author conducted research using normative juridical methods. This juridical approach is because this research analyzes existing legal aspects, and is normative because this research focuses more on the analysis of existing laws and regulations and other regulations, using secondary data, namely scientific references or other scientific papers as study material that can support the completeness of this scientific work. The phenomenon of disruptive innovation that occurs in the financial services industry such as the emergence of fintech has great potential because it can provide solutions to urgent needs that traditional financial institutions cannot provide. Fintech refers to the use of technology to provide financial solutions. Although it is relatively new, Islamic fintech does not have a significant difference with conventional fintech. Because both types want to provide financial services. The difference between the two is only a financing contract which follows the rules of Islamic law. There are three sharia principles that must be owned by this fintech, namely no maisir (betting), gharar (uncertainty) and usury (the amount of interest past the stipulation